Sequenciamento do genoma completo do vírus Culex flavivirus (Flaviviridae) isolado no Brasil - Machado, Daiane Cristina [UNESP] (2014)
In Brazil, the presence of ecosystems with a wealth and diversity of animals, and cities large and densely populated offers conditions for the occurrence of many arboviruses. Several arboviruses transmitted by mosquitoes of the genus Culex belong to the genus Flavivirus. Viruses of this genus are known to cause disease in humans and animals, however, flaviviruses do not infect or cause disease in vertebrates, replicating only in arthropods have been described. Culex flavivirus virus is an example. He was isolated from species of mosquitoes of the genus Culex in North America, Central America, South America, Africa and Asia. Although studies conducted in other parts of the world, in Brazil there is still little information about this virus. In this work we performed the sequencing of the complete genome of Culex flavivirus virus (CxFV) isolated from Culex mosquitoes in São José do Rio Preto (SP) using the techniques of RT-PCR and nucleotide sequencing. The viral genome of the isolated (CxFV_RPBR07_2007) obtained in the present study presented 10.706 nucleotides with an ORF of 10.092 nucleotides (3.364 amino acids) flanked by a 5'UTR of 32 nucleotides and a 3'UTR of 582 nucleotides. Phylogenetic analyzes revealed that the CxFV_RPBR07_2007 groups with other insect flaviviruses such as the Cell fusing agent virus (CFAV) and Kamiti River virus (KRV), and is closely related to CxFV isolates from Mexico (Latin America) and Uganda (Africa); also maintaining relationship with isolates from the United States of America (North America) and Japan (Asia). These groupings were also observed in other phylogenetic studies